Psychological features of students' experience of limited access to social networks - Ирина В. Абакумова; Наталья Е. Комерова; Сергей Н. Рягин (Российский психологический журнал, 2022)
Introduction. Social networks are a tool for finding social contacts, emotional support, a means of self-expression and self-presentation. In the period of so called "crisis of credibility", expressed in a large amount of unverified and often contradictory information, it is very important to study the psychological characteristics of students' experience of limited access to social networks such as Instagram* (a Meta Platforms Inc. project, which is banned in Russia). The study of informational behavior in recent years has acquired particular relevance, which has been realized in a large number of both foreign and russian works. For the first time, an attempt was made to describe the differences in the characteristics of students' experience of limited access to social networks, depending on the actions of respondents after the restriction of access. Methods. The study involved 174 students aged 18 to 21 years (61 boys and 113 girls), students of 1–3 courses of the Don State Technical University. To achieve the goal of the study, the author's questionnaire was used (I. V. Abakumova, N. E. Komerova, S. V. Ryagin); test of Personal Adjustment (K. Rogers, adapted by A. K. Osnitsky); questionnaire "Strategic approach to coping scale" (SACS) (S. Hobfall, adapted by N. E. Vodopyanova, E. S. Starchenkova). Mathematical methods were the statistical Mann-Whitney U-test; Spearman's rank correlation coefficient. Results. Coping strategies and features of socio-psychological adaptation to stressful situations change depending on the actions of respondents after restricting access to the social network Instagram* (continuation of use using VPN applications, termination of use after a ban). Respondents who stopped using the Instagram* social network showed a higher level of avoidance and impulsive actions, less severity of internal control, adaptability, and emotional discomfort than respondents who continued to use this social network. Discussion. Studies of informational behavior by both domestic and foreign authors emphasize the importance of the virtual space of social networks as a way of self-presentation, communication, getting support, self-expression, etc., which is consistent with our results that limiting access to the popular resource among young people (Instagram*) can be perceived as a frustrating event, the loss of a "part" of life, which activates certain coping strategies and mechanisms of socio-psychological adaptation.